Research trends and hotspots of neurodegenerative diseases employing network pharmacology: A bibliometric analysis - Zhu, Jie; Liang, Qingchun; He, Siyi; Wang, Chen; Lin, Xiafei; Wu, Duozhi; Lin, Guanwen; Wang, Zhihua (Frontiers in Pharmacology, 2023)
Background: Employing network pharmacology in neurodegenerative diseases (NDs) has been extensively studied recently. However, no comprehensive study has conducted on this subject employing bibliometrics so far. The purpose of this study was to find out the developmental trends and hotspots, and to predict potential research directions in this filed. Methods: Relevant research were collected from the Web of Science Core Collection(WOSCC). Bibliometrics and visual analysis were executed using CiteSpace, VOSviewer, Histcite and R-bibliometrics. Results: A total of 420 English articles on network pharmacology in NDs published in 2008–2022 were obtained from the WOSCC database. From 2008 to 2022, annual publications showed a steady growing trend , especially in 2014–2022. China, Beijing Univ Chinese Med, Frontiers in Pharmacology, and Geerts H are the most prolific country, institution, journal, and author, respectively. In addition, China, Nucleic Acids Research, and Hopkins AL are the most highly cited country, journal, and author. Moreover, network pharmacology and alzheimers disease are the focus areas of current researches according to analysis of co-cited references and keywords. Finally,“systematic pharmacology”, “database”, “traditional chinese medicine(TCM)”, and “alzheimers disease” as the latest burst keywords are the research frontiers. Conclusion:Network pharmacology and Alzheimers disease are the main topics of researches on network pharmacology in NDs. Systematic pharmacology and the TCM treatment of Alzheimer’s disease have been the recent research hotspots. To sum up, the potential for exploring TCM treatment of AD with network pharmacology is huge.